The 2018–2020 Multi‐Year Drought Sets a New Benchmark in Europe - Rakovec, Oldrich; Samaniego, Luis; Hari, Vittal; Markonis, Yannis; Moravec, Vojtěch; Thober, Stephan; Hanel, Martin; Kumar, Rohini (Earth's future, 2022)
During the period 2018–2020, Europe experienced a series of hot and dry weather conditions with significant socioeconomic and environmental consequences. Yet, the extremity of these multi‐year dry conditions is not recognized. Here, we provide a comprehensive spatio‐temporal assessment of the drought hazard over Europe by benchmarking past exceptional events during the period from 1766 to 2020. We identified the 2018–2020 drought event as a new benchmark having an unprecedented intensity that persisted for more than 2 years, exhibiting a mean areal coverage of 35.6% and an average duration of 12.2 months. What makes this event truly exceptional compared with past events is its near‐surface air temperature anomaly reaching +2.8 K, which constitutes a further evidence that the ongoing global warming is exacerbating present drought events. Furthermore, future events based on climate model simulations Coupled Model Intercomparison Project v5 suggest that Europe should be prepared for events of comparable intensity as the 2018–2020 event but with durations longer than any of those experienced in the last 250 years. Our study thus emphasizes the urgent need for adaption and mitigation strategies to cope with such multi‐year drought events across Europe. Plain Language Summary This manuscript demonstrates that the 2018–2020 multi‐year drought event constitutes a new benchmark in Europe, with an unprecedented level of intensity over the past 250 years. What makes this event truly exceptional compared with past events is its temperature anomaly reaching +2.8 K. This finding provides new evidence that the ongoing global warming exacerbates current drought events. The key message of this study is that the projected future events across the European continent will have a comparable intensity as the 2018–2020 drought but exhibit considerably longer durations than any of those observed during the last 250 years. Our analysis also shows that these exceptional temperature‐enhanced droughts significantly negatively impact commodity crops across Europe. Key Points The 2018–2020 multi‐year drought shows unprecedented level of intensity during the past 250 years The 2018–2020 event reached record‐breaking +2.8 K temperature anomaly and negatively impacted major crops Future drought events reach comparable intensity of 2018–2020 but with considerably longer durations